Analysis on the Social Demand and Training Path of the Aged Service Talents: Take Dazhou City of Sichuan Province as An Example - Zhang, Junpu (Journal of Theory and Practice of Management Science, 2024)
The training of senior service personnel is an important part of the development of senior service industry. The lack of senior service personnel seriously restricts the improvement of senior service quality. At present, there is a large gap in the demand for talents in the elderly care service, the talent structure is unreasonable, and the talent training mechanism is not perfect. In order to better promote the development of pension services, it is necessary to make plans for the construction of pension service talent team as soon as possible, increase preferential policies for the training of elderly service and nursing talents, and vigorously support local colleges and universities to apply for pension service management, nursing and rehabilitation therapy and other related majors, so as to realize the healthy and sustainable development of pension services. This report aims to investigate how can Adidas survive and improve in a consistently changing environment and strong competition. This report focuses on the multi-billion dollar shoe industry in 2021, with green, sustainable, and innovative themes. Sports and fashion will become the trend of the future industry. Adidas' global revenue is 21.23 billion euros, lagging behind the powerful Nike, with a growth rate of 16% compared to 2020, but still lagging behind the level before the 2019 pandemic. A turbulent environment, capturing consumer demand and supply chain management are the main risk issues. The company has made progress in climate change and SDG's, establishing a good brand image, but only 42% of supplier facilities met the standards and lacked the comprehensiveness of goals. They are committed to commercial product innovation, but there is a lack of internal innovation and innovative product sustainability. They opt for a detailed and systematic approach to supply chain management. They also pay attention to employee development and a fair environment, but lack concern for daily life. Adidas has a sound risk management system and has effectively responded to epidemic risks, but measures to address small and potential risks need to be improved. Because they have a certain business scale and continue to work hard, Adidas can survive in the constantly changing environment and competition, but surpassing Nike may require breakthroughs.